Nilai Diagnostik Ultrasonografi Hepatobilier sebagai Prediktor Atresiabilier pada Kolestasis Bayi di RSUP Sanglah Denpasar Tahun 2017 - 2021 - Kristin Agustina; Pande Putu Yuli Anandasari; Firman Parulian Sitanggang; I Wayan Gede Artawan Eka Putra; Made Widhi Asih; Putu Patriawan (Fakultas Kedokteran, Universitas Andalas, 2023)
Hepatobiliary ultrasound is the most common initial diagnostic modality in the early detection of biliary atresia. It is not the gold standard, but the hepatobiliary ultrasound examination can be used to determine the appropriate further management. Objective: To determined the diagnostic value of ultrasound examination as a predictor of biliary atresia in cholestasis of infants. Methods: This was an observational study with a diagnostic test to determine the validity of hepatobiliary ultrasound as a predictor of biliary atresia with cholangiography as the gold standard. The research subjects were 40 infants taken by total sampling from January 2017 until December 2021. Data were obtained from medical records, hepatobiliary ultrasound images were accessed from PACS, and cholangiography results from SIMARS. The hepatobiliary ultrasound images were scored by two observers using a scoring table. The variables assessed included: gallbladder morphology, absence of common bile duct, triangular cord sign, gallbladder contraction index and liver morphology. Data analysis consisted of interobserver reliability test, and relationship assessment analysis. Diagnostic tests to determine the optimal cut-off score, sensitivity, specificity, positive predictive value, negative predictive value and accuracy. Results: At cut-off≥ 5, the number of patients with radiologically impressive biliary atresia was 26 and not biliary atresia was 14. The validity analysis showed a sensitivity 87.5%, specificity 68.8%, positive predictive 80.8%, negative predictive 78.6%, and accuracy 80%. Conclusion: The diagnostic value of hepatobiliary ultrasound as a predictor of biliary atresia in cholestasis of infants is good.Keywords: biliary atresia, hepatobiliary ultrasound, neonatal cholestasis